DEVELOPMENT OF HISTORY E-BOOKS BASED ON HISTORICAL HERITAGE IN ROKAN HILIR TO IMPROVE LEARNING MOTIVATION OF GRADE XI STUDENTS AT SMAN 1 KUBU BABUSSALAM: PENGEMBANGAN E-BOOK SEJARAH BERBASIS PENINGGALAN SEJARAH DI ROKAN HILIR UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS XI DI SMAN 1 KUBU BABUSSALAM - Adia Pratama; Ahmal; Asril (SOSIOEDUKASI, 2025)
This research aims to develop a history e-book based on historical heritage in Rokan Hilir as an innovative learning media to improve students’ learning motivation in history subject for Grade XI at SMAN 1 Kubu Babussalam. The background of this study is the low student engagement in history learning caused by the lack of contextual and interactive teaching materials. The research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data collection techniques included expert validation, student response questionnaires, and motivation assessment before and after using the developed e-book. The results showed that the e-book was categorized as "very feasible" with a material expert validation score of 92% and a media expert validation score of 94%. Student response in small and large group trials also reached a very positive category, with an average of 91%. Moreover, student motivation increased significantly after the implementation of the e-book, demonstrating its effectiveness in engaging learners. The novelty of this research lies in its integration of local historical sites—such as the Rokan Palace, colonial architecture, and traditional Islamic relics—into a digital format, enhancing the relevance and appeal of history lessons. The e-book not only supports curriculum goals but also contributes to the preservation and promotion of local cultural heritage through education.